The Implementation of Task-Based Learning Strategy by Making Video Introduction to Improve Students’ Speaking Skills - Dewi Khawa Khawa; Faiqotur Rizkiyah (Darussalam English Journal (DEJ), 2022)
This study uses CAR design of the research by using a qualitative approach. The purpose of this study was to find out the application of a task-based learning strategy by making introductory videos in students' speaking skills. Researchers made observations in the preliminary study to find out the problems faced by students in learning speaking. In the first cycle, the researchers had two meetings while in the second cycle the researchers had four meetings. The researchers started the teaching-learning activity by greeting, praying together, checking attendance. Then, the researchers delivered the material that has been determined, displayed a video and PPT related to the material, and gave question and answer session. After that, the researchers gave the task to the students to make an introductory video. The results of this study indicate that the application of a task-based learning strategy by making an introductory video for class VII SMPN 2 Siliragung has a positive impact on students’ speaking achievement. This is evidenced by the average number of students who has increased in each cycle. In the preliminary study, the average number of students' achievement was 62, then increased to 68 in the first cycle and increased to 80 in the second cycle. Thus, this research is declared successful because the results obtained by students in the second cycle have met the predetermined success criteria (70).